2015
DOI: 10.1002/chem.201406227
|View full text |Cite
|
Sign up to set email alerts
|

Decarbonylative CC Bond‐Forming Reactions of Saccharins by Nickel Catalysis: Homocoupling and Cycloaddition

Abstract: Decarbonylation of saccharins by nickel catalysis enables two kinds of CC bond-forming reactions; homocoupling of saccharins to form biaryls and cycloaddition with alkynes to form benzosultams. The former represents the first reported nickel-catalyzed decarbonylative CC homocoupling reaction, whereas the latter constitutes a powerful method to pharmaceutically relevant benzosultams. The reactions proceed with good functional-group tolerance and excellent regioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 102 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…The facile synthesis via the C–H functionalization catalyzed by Rh, Co, and Pd complexes with simple substrates has dominated in this field over the past decade. Transition-metal catalysis associated with the intermolecular cyclizations through a bond cleavage by the oxidative addition or the intramolecular cyclizations through a C–N bond formation has also demonstrated the feasibility to form diverse sultam derivatives. Meanwhile, the photoinduced radical annulations were reported mainly for the construction of biaryl sultams .…”
mentioning
confidence: 99%
“…The facile synthesis via the C–H functionalization catalyzed by Rh, Co, and Pd complexes with simple substrates has dominated in this field over the past decade. Transition-metal catalysis associated with the intermolecular cyclizations through a bond cleavage by the oxidative addition or the intramolecular cyclizations through a C–N bond formation has also demonstrated the feasibility to form diverse sultam derivatives. Meanwhile, the photoinduced radical annulations were reported mainly for the construction of biaryl sultams .…”
mentioning
confidence: 99%
“…A high yield was also obtained at lower catalyst loadings (1.0 mol %) with a prolonged reaction time (entry 15). Notably, other commonly used transition‐metal catalysts for decarbonylation, such as Ni(COD) 2 , [9a–d,g] Co 2 (CO) 8 , [18] Pd(PPh 3 ) 4 , [8] did not afford any desired product, which indicates the unique property of Rh in the photo‐induced decarbonylative reactions (entries 16–18).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to phthalimides, decarbonylative cycloaddition has also been achieved by using saccharins as the substrate. In 2015, Bi et al reported the Ni-catalyzed decarbonylative cycloaddition between saccharins 250 and alkynes 169 (Scheme 96); 254 decarbonylative homocoupling was also developed in this work. Mechanistically, the oxidative addition of Ni and extrusion of CO were key steps for both procedures.…”
Section: Decarbonylation With Cleavage Of C(acyl)−n/c(acyl)−c Bondsmentioning
confidence: 99%